(untitled) (The Pakistan Development Review, 1992)
This paper is a follow up in the Pakistani context of the issues raised in UNICEFs classic contribution to the political economy of development, Adjustment With a Human Face [Cornia, Jolly and Stewart (1987), henceforth AWHF]. It tries to set out the issues involved in understanding why despite four decades of development has there not been a significant move towards meeting the basic needs of the population. Our argument is that reliance on the cultural norms of justice and humanness - particularly as regards vulnerable groups - as the basis of choosing priorities and designing policies, is a means and not an obstacle to systainable growth and structural adjustment. Structural adjustment, namely changes in a untry’s production and consumption structure, becomes necessary when expenditures begin to exceed incomes systematically. However, orthodox adjustment programmes have often been criticised because they have tended to retard growth in poor countries, and to shift the burden onto vulnerable groups. In the tradition of this literature, we argue not against the necessity of structural adjustment, but against the adverse entailments of such adjustment. Hence the title, "Just Adjustment".